8 - Successful ageing amongst elderly women living independently in central areas Of Pretoria, South Africa - Marlize Rabe (African Sociological Review, 2015)
This qualitative study explores successful ageing among a group of old women who live in the central areas of Pretoria in South Africa. It utilised the notion of successful ageing as a theoretical construct to examine how the women adapt to the challenges of old age. The study reveals that participants who had overcome difficult challenges in previous life stages by relying on their own resources are the most likely to adjust comfortably to the challenges of old age as well as the complexities encountered in the diverse central areas of Pretoria